Impaired Nicotinamide Adenine Dinucleotide Biosynthesis in the Kidney of Chronic Kidney Disease - Liu, Xinhui; Luo, Denggui; Huang, Shiying; Liu, Siqi; Zhang, Bing; Wang, Fochang; Lu, Jiandong; Chen, Jianping; Li, Shunmin (Frontiers in Physiology, 2021)
Chronic kidney disease (CKD) is a global public health problem with high morbidity and mortality. Decreased nicotinamide adenine dinucleotide (NAD+) levels were found to be associated with aging, cancer, and neurodegenerative and metabolic disorders. However, the alteration of renal NAD+ levels and biosynthesis pathways in CKD are less known. In the present study, we aimed to evaluate renal NAD+ levels and tested the expression of key enzymes in three NAD+ biosynthesis pathways in two different types of CKD rat model. CKD rat models were established by 5/6 nephrectomy (5/6 Nx) and feeding with adenine-containing feed, respectively. Renal function was assessed by serum creatinine (Scr) and blood urea nitrogen (BUN). Renal pathology was evaluated by Periodic acid-Schiff (PAS) and Masson’s trichrome staining. The expression of key enzymes in three NAD+ biosynthesis pathways were determined and quantified by Western blot analysis. The results showed CKD rat models were successfully established as evidenced by increased Scr and BUN levels, up-regulation of neutrophil gelatinase-associated lipocalin (NGAL), glomerular hypertrophy and renal fibrosis. Renal NAD+ and NADH content were both declined in two CKD rat models, and NAD+ levels were negatively correlated with Scr and BUN levels in CKD rats. Three key enzymes involved in NAD+ biosynthesis were significantly down-regulated in the kidney of both of the two CKD models. They were quinolinate phosphoribosyltransferase (QPRT) in the de novo pathway, nicotinamide mononucleotide adenylyltransferase 1 (NMNAT1) and NMNAT3 in the salvage pathway. Moreover, the expression of NAD+-consuming enzymes sirtuin 3 (SIRT3) and CD38 decreased significantly in CKD rats. In conclusion, NAD+ biosynthsis was significantly impaired in CKD, which may attribute to down-regulation of QPRT and NMNAT 1/3.